Determination of Metformin Hydrochloride in Pharmaceutical Formulations - K. Sharma, Vipin; Bhattacharya, A. (Asian Journal of Chemistry, 2010)
Metformin hydrochloride is an antidiabetic drug of biguanide category with multiple benefits in type II diabetes mellitus e.g., lowering of HbA1c values, lipid profile regulation and improvement in vascular and hemodynamic indices. Adverse effects are generally tolerable and self-limiting. Alone as well as in combination with other antidiabetic drugs of different categories, it is administered in different formulations. Due to short biological half-life (2-6 h), it is available in sustained release formulations. The present study concentrates on the various analytical methods of metfromin hydrochloride determination in dosage forms as well in blood plasma.